Maternal Knowledge and Behavior in Relation to Compliance with Complete Basic Immunization among Children Under Five: A Literature Review - Januario de Carvalho Gama; Wahyu Endang Setyowati; Iskim Luthfa; Dyah Wiji Puspita Sari (Indonesian Journal of Global Health Research, 2026)
Compliance with complete basic immunization among children under five remains a public health concern, with maternal knowledge and behavior identified as important influencing factors. This literature review aimed to synthesize quantitative evidence on the association between maternal knowledge and behavior and compliance with complete basic immunization among under-five children. A systematic literature review was conducted following PRISMA guidelines. Searches were performed in PubMed, ScienceDirect, and Google Scholar for open-access articles published between 2020 and 2025. A total of 1,012 articles were identified; after removing 300 duplicates, 712 articles were screened by title and abstract. Of these, 521 articles were excluded, and 191 were assessed for full-text eligibility, with 171 articles unavailable in full text. Twenty articles underwent full assessment, and 16 cross-sectional studies met the inclusion criteria based on study design, participant characteristics, and data completeness. Methodological quality was evaluated using the JBI Critical Appraisal Checklist, and data were synthesized using a quantitative narrative approach. The majority of studies reported a significant association between maternal knowledge and behavior and compliance with complete basic immunization, although adjustment for confounding variables was limited. Maternal knowledge and behavior are closely associated with immunization compliance. Further longitudinal and intervention-based studies are recommended to strengthen causal evidence.